EVALUATION OF ONLINE PASSPORT REGISTRATION APPLICATION SYSTEM (APAPO) AT THE IMMIGRATION OFFICE CLASS II NON BORDER CONTROL DEPOK - Rofiqi Dita Hapsari (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2020)
Indonesia as a developing country continued trying to create new innovations in all aspects, among which was introducing information technology to immigration field. Information technology in immigration was indeed a challenging study for its function to public services. An example of this public service thing was passport services, which quality performance is something demanded to be developed. Introducing passport service with information technology was also helping to increase work’s effectiveness and efficiency and made it took role in the digital era. An innovations made with information technology, which had been introduced throughout Indonesia was an Online Passport Queue Application (APAPO). The study was aimed to evaluate the use of APAPO and to provide appropriate recommendations to improve the system. The study employed a qualitative research methodology with a descriptive approach. The study observed the process of APAPO from the very start to the end. APAPO was introduced to its latest version, which was version 2.0. APAPO received both postive and negative responses from public users.